PENGEMBANGAN MODEL PENERIMAAN PENGGUNA APLIKASI TIX.ID MENGGUNAKAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) DAN ANALISIS SEM - Muhammad Tanzil Kaila; Rini Nuraini (FAKULTAS TEKNIK, 2026)
The development of information technology has transformed people's behavior in accessing online entertainment services. One of the widely used innovations is Tix.id, a cinema ticket booking application developed by PT Nusantara Elang Sejahtera, part of the Emtek Group, in 2018 in collaboration with Bioskop XXI. This study aims to analyze the level of user acceptance of Tix.id using the Technology Acceptance Model (TAM), which includes the variables Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Attitude Toward Using (ATU). The analysis was conducted using the Structural Equation Modeling (SEM) approach with AMOS software based on questionnaire data from active users in Jakarta. The results indicate that all relationships among variables are positive and significant, with Chi-square = 38.06; df = 41; p = 0.60213; RMSEA = 0.000, indicating that the model demonstrates a good fit. These findings suggest that perceived ease of use and perceived usefulness have a strong influence on users’ attitudes toward using the Tix.id application.